Neurophysiological correlates of executive function: a comparison of european-canadian and chinese-canadian 5-year-olds - Ayelet Lahat; Rebecca Todd; Rebecca Todd; Caitlin E V Mahy; Karen Lau; Philip D Zelazo (Frontiers in Human Neuroscience, 2010)
This study explored the neurophysiological correlates of executive function (EF) in young children from 2 different cultural backgrounds. 20 European-Canadian and 17 Chinese-Canadian 5-year-olds participated in a go/no-go task, during which high-density EEG data were recorded. No cultural group differences were observed in children’s behavioral performance on the task, but marked differences were revealed by ERP analyses, which focused on the amplitude and latency of the N2 waveform. Chinese-Canadian children showed larger N2 amplitudes than European-Canadian children on the right side of the scalp on no-go trials, as well as on the left side of the scalp on go trials, and for all children, larger (i.e., more negative) N2 amplitudes were associated with faster median reaction times (RTs). Source analyses of the N2 were consistent with the hypothesis that compared to European-Canadian children, Chinese-Canadian children showed more activation in dorsomedial, ventromedial, and (bilateral) ventrolateral prefrontal cortex. These findings reveal that EEG can provide a measure of cultural differences in neurocognitive function that is more sensitive than behavioral data alone; that Chinese-Canadian children show a pattern of hemispheric differentiation in the context of this task than that is more pronounced than that of age-matched European-Canadian children; that the asymmetrically lateralized N2 may be a reliable marker of both effortful inhibition (on the right) and effortful approach (on the left); and that the neural correlates of EF may vary across samples of healthy participants, even in children.